2018
DOI: 10.1039/c8ra04627a
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gut microbiota between silkworms (Bombyx mori) reared on fresh mulberry (Morus albavar. multicaulis) leaves or an artificial diet

Abstract: Artificial diets for silkworms have many potential applications and they are important in sericulture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 66 publications
6
44
0
Order By: Relevance
“…Enterobacteriaceae dominated the gut bacteria of S. litura feeding on taro leaves, while Pseudomonadaceae dominated the gut bacteria of S. litura feeding on the artificial diet. Similar results have been found with silkworm in which differences in the gut microbes are seen for those feeding on mulberry leaves or artificial diet with these differences leading changes in nutritional metabolism and immune resistance ( Dong et al, 2018 ). A study in pine processionary moth, Thaumetopoea pityocampa , also revealed that different host plants lead to a different gut bacterial community ( Strano et al, 2018 ).…”
Section: Discussionsupporting
confidence: 81%
“…Enterobacteriaceae dominated the gut bacteria of S. litura feeding on taro leaves, while Pseudomonadaceae dominated the gut bacteria of S. litura feeding on the artificial diet. Similar results have been found with silkworm in which differences in the gut microbes are seen for those feeding on mulberry leaves or artificial diet with these differences leading changes in nutritional metabolism and immune resistance ( Dong et al, 2018 ). A study in pine processionary moth, Thaumetopoea pityocampa , also revealed that different host plants lead to a different gut bacterial community ( Strano et al, 2018 ).…”
Section: Discussionsupporting
confidence: 81%
“…Sequences were grouped into OTUs at a 97% similarity level using UPARSE [ 45 ]. The ribosomal database project (RDP) classifier (Version 16) was used to assign sequences to different taxonomic groups based on the Greengene ribosomal RNA gene database (Version 13.5) [ 46 ]. The sequences were submitted to the Sequence Read Archive in National Center for Biotechnology Information (NCBI, ; accession numbers SRR11206458–SRR11206466).…”
Section: Methodsmentioning
confidence: 99%
“…And we found that the butanoic acid content in AF feces was 13.56 times higher than that of the MF feces. The intestinal microbial community diversity of silkworm larvae fed with artificial diet was lower than that of silkworm larvae fed with mulberry leaves [43]. It would be interesting to further explore which gut microbiota causes the intestinal butanoic acid produced after silkworms reared with artificial diets, which further affected the growth and development of the artificial diets-fed silkworm.…”
Section: Certain Metabolites Were More Abundant In the Feces Of The Amentioning
confidence: 99%